Gambaran Pengetahuan, Sikap dan Keterampilan Perilaku Hidup Bersih Sehat (PHBS) Pada Anak Usia Sekolah - Lita Heni Kusumawardani; Arindi Ayuanita Saputri (Jurnal Ilmiah Ilmu Keperawatan Indonesia, 2020)
Abstract Introduction: School age children are population at risk for health problems such as diarrhea. However, the school age children period is the starting point for developing healthy behaviors so that becomes a strategic target of health education. Objective: The study aimed to determine clean and healthy knowledge, attitude, and practice on school age children (6-12 years). Method: The study method used descriptive study with crossectional approach. The subjects was 76 school age children . The sampling technique used multistage random sampling to determine research area while the research target sample used simple random sampling. Instruments used modification clean and healthy behavior questionnaire. Data analysis used descriptive analytics method. Results: The results showed that 60,5% mayority of respondent have a poor level of knowledge with mean 7,78, 53,9% mayority of respondent have a poor level of attitide with mean 29,16, and 65,79% mayority of respondent have a poor level of practise with mean 28,64. The parent of respondent mayority have 57,90% have a poor level of knowledge with mean 8,07. Conclusion: It’s recomended to develop effective health education programs to diarrhea prevention behavior on school age children